Interactions between rheumatoid arthritis synovial fibroblast migration and endothelial cells. Issue 2 (2nd November 2018) - Zimmermann‐Geller, Birgit; Köppert, Sina; Kesel, Nina; Hasseli, Rebecca; Ullrich, Sebastian; Lefèvre, Stephanie; Frommer, Klaus; Gehrke, Thorsten; Schönburg, Markus; Rehart, Stephan; Schumacher, Udo; Müller‐Ladner, Ulf; et al.
Abstract: Leukocytes travel within the circulation and enter connective tissues by interactions with endothelium of postcapillary venules mediated by cell adhesion molecules, summarized as the leukocyte adhesion cascade. In the severe combined immunodeficient (SCID) mouse model, rheumatoid arthritis (RA) synovial fibroblasts (SF) migrated to distant cartilage through the vasculature. Therefore, RASF adhesion toward endothelial cells (EC) and E‐ and P‐selectins were analyzed. Cell‐to‐cell binding assays between SF and EC were performed. Interactions of SF with tumor necrosis factor α (TNFα)‐activated EC or selectins were analyzed in flow adhesion assays. Immunohistochemistry for E‐selectin ligand CD15s was performed. CD15s induction in RASF by human serum or media was evaluated. Wild‐type and E ‐/‐/ P ‐/‐ Selectin‐SCID mice were used for inverse‐wrap surgery. After laser‐mediated microdissection, real‐time PCR for E‐/P‐selectin/vascular cell adhesion molecule 1 was performed. Adhesion between SF/EC under static conditions was highest in Roswell Park Memorial Institute‐cultured RASF to TNFαα‐activated human umbilical vein endothelial cells (2.25‐fold) and RASF adhesion was higher toward venous than arterial EC (Dulbecco's modified eagle medium P = 0.0419, RPMI P = 0.0119). In flow chamber assays, RASF adhesion to E‐selectin was higher than to P‐selectin (e.g. 0.9 dyn cm −2 P = 0.0001). Osteoarthritis synovial fibroblasts showed lower rolling/adhesion properties (e.g. 0.5 dyn cm −2, P = 0.0010). RASF adhesion to TNFαα‐activated EC was increased (e.g. 0.9 dyn cm −2, P = 0.0061). CD15s induction in RASF was strongest in RA serum. Vimentin/CD15s double‐positive cells were detectable. In E‐/P‐selectin‐deficient mice, contralateral invasion was reduced ( P = 0.023). E‐ and P‐selectin, and vascular cell adhesion molecule 1 expression in EC of implants was confirmed. Our data indicate that the milieu within vessels induces CD15s which enables RASF to interact with E‐selectin/EC under flow. Therefore, RASF may migrate to distant sites and leave the vasculature similarly to leukocytes. Abstract : Rheumatoid arthritis synovial fibroblasts migrate to distant cartilage through the vasculature. Therefore, RASF adhesion toward endothelial cells (EC) and E‐ and P‐selectins was analyzed. The milieu within blood vessels induces CD15s which enables RASF interaction with E‐selectin/EC under flow conditions and thus helps RASF leave the vasculature similarly to leukocytes.